ADAR-editing during Ostreid herpesvirus 1 infection in Crassostrea gigas: facts and limitations - Umberto Rosani; Enrico Bortoletto; Caroline Montagnani; Paola Venier (mSphere, 2022)
Ostreid herpesvirus-1 (OsHV-1) RNAs are enzymatically modified by A-to-I conversions during the infection of Crassostrea gigas. The increase of ADAR1 expression and hyper-editing activity parallel to OsHV-1 RNAs suggests a functional connection between dsRNA editing and antiviral responses. We analyzed 87 RNA-seq datasets from immuno-primed, resistant, and susceptible oysters exposed to OsHV-1 to compare the ADAR hyper-editing levels on host and viral transcripts and trace hyper-editing on the oyster genes. Host RNAs were more hyper-edited than viral RNAs, despite the increased editing of viral RNAs in late infection phases. A set of genes, representing ~0.5% of the oyster transcriptome and including several Tripartite motif-containing sequences, were constantly hyper-edited. Conversely, we identified genes involved in antiviral response, miRNA maturation and epigenetic regulation which were hyper-edited in specific conditions only. Despite technical and biological bottlenecks that hamper the understanding of the bivalve ‘RNA editome’, available tools and technologies can be adapted to bivalve mollusks.